Pranata Mangsa Kearifan Lokal Suku Jawa di Medan Tembung Dalam Menjaga Pola Tanam - Dora, Nur Iza; Yanzhuri, Mhd; Rivaldi, Taufik; Sholihin, Muhammad (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This research examines the local wisdom practices of the Javanese tribe in Medan Tembung in maintaining cropping patterns. The aim of this research is to illustrate how traditional values still function amidst the challenges of climate change and urbanization, while inspiring approaches that combine modern technology and local traditions for more adaptive and environmentally friendly food security. This research uses a qualitative approach. The research method applied is descriptive using data collection techniques through observation, interviews and documentation. The results of this research Pranata Mangsa acts as a traditional guide for the Javanese people in Medan Tembung in farming, helping determine appropriate planting and harvest times. according to weather conditions and recognizing natural signs. Apart from being a practical guide, Pranata Mangsa is also local wisdom passed down through agricultural culture and rituals. However, its preservation is now threatened by the lack of interest of the younger generation who are more interested in modern technology, climate change which disrupts seasonal patterns, and the lack of formal support, all of which makes it difficult to regenerate this knowledge amidst the rapid development of the world of agriculture.